Linkage in extra-sensory perception - Marsh, Maurice Clement (Rhodes University, Faculty of Humanities, Department of Psychology, 1959)
The aims of this investigation were firstly to find whether 371 subjects, mainly students at Rhodes University, would be able to reproduce target drawings made 470 miles away by an agent in Cape Town, by means of General Extra-Sensory Perception; secondly, to find whether any association existed between any such hit scoring ability shown and personality ratings derived from a battery of personality test material; and thirdly, to find whether providing the subjects with material designed to link them more closely with the agent would increase their scoring rate. The 17,440 drawings returned by the subjects were randomised, and scored against a randomised set of 100 drawings consisting of 50 which had actually been used as targets, intermixed with 50 that were equal in difficulty but which had not been used as targets, and which were inserted merely as controls. Three independent judges assessed the subjects' drawings, and awarded hits in terms of title, shape and association. In the crucial title hits highly significant deviations in favour of the experimental target drawings were found, the control series of drawings showing no such effects. It was found that the subjects' hits were distributed evenly throughout the whole 25 day period of the experiment for each target, and showed no tendency to occur more frequently in the week a particular drawing was being used as a target than in the other weeks when it was not. When the subjects were divided into a high scoring and low-scoring group in terms of their E.S. P. abiility, the high- scoring group proved to be significantly more extraverted (as measured by the Bernreuter B3I scale) than the low- scoring group, confirming a relationship previously reported by Humphrey. In addition the data showed several other relationships, predicted by the work of previous experimenters, although these did not reach the .01 level of statistical significance. To assess the effect of the Linkage Material the subjects were divided into an experimental and a control group. The Experimental Group was supplied with correct Linkage Material, the Control Group with incorrect Linkage Material, which they were led to believe was correct . The two sets of Linkage Material were equated in all other respects. The Experimental Group showed significant improvements in scoring rate when supplied with a photograph and description of the agent, and a probably significant improvement when supplied with squares of handkerchief which had previously belonged to him. When supplied with squares of colour, also appearing on the agent's target sheets, no significant increase in scoring rate took place on the target drawings, but a significant decrease occurred in hits scored on the control targets. By contrast no consistent significant fluctuations were shown by Control Group Subjects, leading to the conclusion that the correctness of the Linkage Material was a factor contributing to its effectiveness. A qualitative examination of the hits scored by the subjects revealed that they tended to reproduce the concepts depicted by the target drawings, rather than the actual shapes drawn by the agent, suggesting that the hits were being produced by a telepathic process rather than a clairvoyant one. The results of the experiment suggest that the subjects were assisted by the Linkage Material to gain access to the agent's mind as a whole, and not to particular items in it. This throws doubt on the correctness of Whately Carington's Association Theory of Telepathy, which the experiment was designed to test.
Keywords: Telepathy; Extrasensory perception